Assessment of ICD-11 Personality Disorder Severity in Forensic Patients Using the Semi-structured Interview for Personality Functioning DSM-5 (STiP-5.1): Preliminary Findings - Hutsebaut, Joost; Weekers, Laura C.; Tuin, Nynke; Apeldoorn, Jessica S. P.; Bulten, Erik (Frontiers in Psychiatry, 2021)
In forensic settings, several challenges may affect reliability of assessment of personality pathology, specifically when based upon self-report. This study investigates the Semi-Structured Interview for DSM-5 Personality Functioning (STiP-5.1) to assess level of severity of personality functioning in incarcerated patients. Thirty inpatients of three forensic psychiatric facilities completed the STiP 5.1 and additionally completed self-report questionnaires assessing symptom severity, personality functioning and traits. Staff members completed informant versions of personality functioning questionnaires. Previously assessed community (N = 18) and clinical samples (N = 80) were used as a reference. Interrater reliability and internal consistency of the STiP 5.1 were good. As expected, no associations were found between self-report and expert-ratings (STiP 5.1) of personality functioning. Remarkably, no associations were found between informant rated personality functioning and the STiP 5.1. This study confirms the discrepancies between self-report and expert-ratings in forensic settings and identifies the need to design and test assessment instruments within this context instead of generalizing findings obtained in regular mental health care samples. The STiP-5.1 may be a candidate for use in forensic samples, more particularly to guide treatment planning and individual patient policy, although it remains unclear what specific information it offers above and beyond self-report and informant-report.